The Role of Customer Satisfaction and Service Quality on Loyalty of Bank Customers - Rohana, Siti (Journal of Industrial Engineering & Management Research, 2019)
The purpose of this study was to analyze the relationship between service quality and customer satisfaction, to analyze the relationship between service quality and customer loyalty, and to analyze the relationship between customer satisfaction and customer satisfaction. Data analysis in this study used Structural Equation Modeling (SEM) analysis with SmartPLS software. The population in this study were bank customers using e-banking in Tangerang. The sample in this study was taken from the existing population. and at least have used a bank in the form of sms banking, call banking, ATM, and internet banking. The technique for taking the sample is using a non-probability sampling technique, in this case judgment sampling, which is a convenience sampling form. Thus, the number of samples in this study were 500 respondents who had used e-banking services. The results of this study are that there is a positive and significant relationship between service quality and customer satisfaction, there is a positive and significant relationship between service quality and customer loyalty, there is a positive and significant relationship between customer satisfaction and customer satisfaction.